2006
DOI: 10.1161/circulationaha.105.602870
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multiple Mechanisms in Human Ventricular Fibrillation

Abstract: Background-The mechanisms that sustain ventricular fibrillation (VF) in the human heart remain unclear. Experimental models have demonstrated either a periodic source (mother rotor) or multiple wavelets as the mechanism underlying VF. The aim of this study was to map electrical activity from the entire ventricular epicardium of human hearts to establish the relative roles of these mechanisms in sustaining early human VF. Methods and Results-In 10 patients undergoing cardiac surgery, VF was induced by burst pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
199
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(223 citation statements)
references
References 26 publications
20
199
0
4
Order By: Relevance
“…First direct experimental observations of such states were reported almost 20 years ago 6,7 . Recent experimental and simulations studies 8,9 show a complex picture with states dominated by one or a few mother rotors as well as multiple wave dynamics characterized by a mean number of 10 vortices on the surface of, e. g., a human heart. The fluctuations in vortex number resemble a Poissonian statistics.…”
Section: Introductionmentioning
confidence: 99%
“…First direct experimental observations of such states were reported almost 20 years ago 6,7 . Recent experimental and simulations studies 8,9 show a complex picture with states dominated by one or a few mother rotors as well as multiple wave dynamics characterized by a mean number of 10 vortices on the surface of, e. g., a human heart. The fluctuations in vortex number resemble a Poissonian statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Others believe that fibrillation is maintained by the constant creation and annihilation of wavelets which occur due to functional and anatomical heterogeneities (Choi et al, 2002;Lee et al, 1996;Moe, 1962;Rogers et al, 1999;Valderrábano et al, 2002). More recently, some groups have concluded that fibrillatory activity may be driven by both mechanisms, depending on specific conditions in the heart Liu et al, 2004;Nash et al, 2006;Wu et al, 2002). Mutual information techniques have been used to examine the relationship between V m and Ca i .…”
Section: Pre/post-conditioning Of Optical Datamentioning
confidence: 99%
“…Problems in the electrical system of the heart may result in cardiac arrhythmias, e.g. rapid activation and spatial desynchronization of mechanical contractions in the heart, (26,30) which cause the mechanical pump function of the heart to malfunction. In the US alone, more than 450,000 people die suddenly each year as a result of cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 99%